Neurological manifestations of encephalitic alphaviruses, traumatic brain injuries, and organophosphorus nerve agent exposure - VanderGiessen, Morgen; de Jager, Caroline; Leighton, Julia; Xie, Hehuang; Theus, Michelle; Johnson, Erik; Kehn-Hall, Kylene (Frontiers in Neuroscience, 2024)
Encephalitic alphaviruses (EEVs), Traumatic Brain Injuries (TBI), and organophosphorus nerve agents (NAs) are three diverse biological, physical, and chemical injuries that can lead to long-term neurological deficits in humans. EEVs include Venezuelan, eastern, and western equine encephalitis viruses. This review describes the current understanding of neurological pathology during these three conditions, provides a comparative review of case studies vs. animal models, and summarizes current therapeutics. While epidemiological data on clinical and pathological manifestations of these conditions are known in humans, much of our current mechanistic understanding relies upon animal models. Here we review the animal models findings for EEVs, TBIs, and NAs and compare these with what is known from human case studies. Additionally, research on NAs and EEVs is limited due to their classification as high-risk pathogens (BSL-3) and/or select agents; therefore, we leverage commonalities with TBI to develop a further understanding of the mechanisms of neurological damage. Furthermore, we discuss overlapping neurological damage mechanisms between TBI, NAs, and EEVs that highlight novel medical countermeasure opportunities. We describe current treatment methods for reducing neurological damage induced by individual conditions and general neuroprotective treatment options. Finally, we discuss perspectives on the future of neuroprotective drug development against long-term neurological sequelae of EEVs, TBIs, and NAs.